2012
DOI: 10.4049/jimmunol.1100218
|View full text |Cite
|
Sign up to set email alerts
|

Contact-Dependent Interference with Invariant NKT Cell Activation by Herpes Simplex Virus-Infected Cells

Abstract: Invariant CD1d-restricted natural killer T (iNKT) cells play important roles in generating protective immune responses against infections. Here, we have investigated the role of human iNKT cells in HSV-1 infection and their interaction with epidermal keratinocytes. These cells express CD1d and are the primary target of the virus. Keratinocytes loaded with α-GalCer could stimulate IFN-γ production and CD25 upregulation by iNKT cells. However, both α-GalCer- and cytokine-dependent activation of iNKT cells was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 69 publications
2
19
0
Order By: Relevance
“…2A). Consistent with previous reports (6,25,33,45), an HSV-1 infection reduced the ability of CD1d molecules to recycle back to the cell surface (Fig. 2B).…”
Section: Vp22 Is Important For Inhibiting Cd1d Recycling Upon An Hsv-supporting
confidence: 81%
See 1 more Smart Citation
“…2A). Consistent with previous reports (6,25,33,45), an HSV-1 infection reduced the ability of CD1d molecules to recycle back to the cell surface (Fig. 2B).…”
Section: Vp22 Is Important For Inhibiting Cd1d Recycling Upon An Hsv-supporting
confidence: 81%
“…We and others have shown that HSV-1 can inhibit CD1d-mediated antigen presentation to NKT cells by suppressing CD1d recycling (6,25,33,45). This inhibition of NKT cell function by HSV-1 is dependent on cell-to-cell contact of infected APCs and NKT cells, but not due to infection of NKT cells (6).…”
mentioning
confidence: 99%
“…Upon infection of CD1d + cells by many viruses, including varicella virus, vesicular stomatitis virus and HIV, CD1d molecules are reduced on the cell surface . Infections by HSV, like those by other viruses, also suppress CD1d‐mediated activation of NKT cells, probably by inhibiting the transport of newly synthesized CD1d molecules to the cell surface …”
Section: Introductionmentioning
confidence: 99%
“…HSV-1 is known to interfere with CD1d Ag presentation (10,11,28) and to impair TCR signaling in iNKT cells (9). In contrast, mice are more resistant to HSV-associated immune evasion mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with human cells have shown that HSV-1 interferes with CD1d Ag presentation and NKT cell activation (9)(10)(11). Finally, there is direct evidence from murine HSV-1 and HSV-2 infection models that iNKT cells contribute to virus control (12,13).…”
mentioning
confidence: 99%